Education for Sustainable Develoment (ESD) – Pancasila di Desa Towangsan: Paradigma Pembangunan yang Berkelanjutan - Sindung Tjahyadi; Andhika Djalu Sembada; Hastangka Hastangka; Yesika Theresia Sinaga (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
ABSTRACT The village of Towangsan, Gantiwarno, Klaten district, Central Java has the potential of social, cultural and local economic capital that can serve as a model and application to continually maintain the values of locality, sustainable development values based on the identity and personality of the Indonesian nation namely Pancasila. Pancasila became the basic moral and basic values in formulating village development policy in Towangsan Gantiwarno village, Klaten regency, Central Java. Community service activities with ESD implementation framework in society implemented by UGM Pancasila Study Center is to design and formulate Indonesia-based Center for Innovation and Education for Sustainable Development (ESD) based on Pancasila values. The Center for Innovation and Development of Education for Sustainable Development is to provide the foundation and commitment of the village community in order to work consciously and continuously actualize the values of sustainable development in accordance with the areas that are involved such as Lare mentes community based culture community, and Karang Taruna based sustainable development. The results achieved in this activity are the establishment of a community-based ESD Innovation and Development Center in Towangsan Gantiwarno Village, community awareness of the importance of sustainable development, and the documentation of Towangsan village profiles based on Pancasila values. Implementation of ESD-Pancasila Implementation also has a positive impact in Towangsan because it has changed the mindset and way of thinking of the exclusive from the exclusive. Keywords: ESD; Pancasila; sustainable development.